Lysmata jundalini, a new peppermint shrimp (Decapoda, Caridea, Hippolytidae) from the Western Atlantic - Rhyne, Andrew L.; Calado, Ricardo; Santos, Antonina Dos (Zootaxa, 2012)
A new peppermint shrimp species, Lysmata jundalini sp. nov., is described based on five specimens collected in shallowsubtidal waters on Enrique Reef at the University of Puerto Rico, Mayagüez Isla, Magueyes Laboratories. Lysmata jund-alini sp. nov. was identified from fresh material collected at the reef crest and back reef among coral rubble in June 2005and April 2009. The new species is most closely related to the Atlantic Lysmata intermedia and eastern Pacific L. holthu-isi. It can be readily distinguished from all those in the genus Lysmata by its color pattern, the presence of a well developedaccessory branch, the number of free vs. fused segments of the accessory branch, the number of carpal segments of the second pereiopod and well developed pterygostomian tooth.